أثر حاضنات الأعمال الجامعية على تجسيد القرار الوزاري 1275 - دراسة حاضنة جامعة الوادي - سعداني محمد البشير; صالحي ناجية (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى تقييم مدى نجاج حاضنات الأعمال الجامعية في تحقيق الأهداف الموسومة في القرار الوزاري 1275 المؤرخ في 27 سبتمبر 2022 ، أجريت الدراسة على عينة مستهدفة مكونة من 74 طالب مسجل في الحاضنة الجامعية لجامعة الوادي، ضمن مشروع مذكرة التخرج شهادة جامعية -مؤسسة ناشئة ولتحقيق هذا الغرض استخدم الباحثان المنهج الوصفي والتحليلي والاستبانة كأداة لجمع البيانات و معالجتها و إختبار الفرضيات توصلت الدراسة إلى أن هناك أثر بنسبة 37 % للحاضنة الجامعية في تحقيق أهداف القرار الوزاري 1275 بشكل يلائم متطلبات البيئة الحديثة للجامعة والمحيط وهذا راجع لحداثة القرار و الألية الجديدة للتخرج بدلا من نمطية شهادة و البحث عن العمل، أصبح الطالب ريادي مستحدث لفرص العمل.This study aims to evaluate the extent of the success of university business incubators in achieving the goals set forth in Ministerial Resolution 1275 of September 27, 2022. The study was conducted on a targeted sample of 74 students registered in the university incubator at El-Oued University, within the framework of the University Certificate Graduation Memorandum Project - Foundation. To achieve this purpose, the researchers used the descriptive and analytical approach and the questionnaire as a tool for collecting data, processing it, and testing hypotheses. The study concluded that there is an impact of 37% for the university incubator in achieving the goals of Ministerial Resolution 1275 in a manner that suits the requirements of the modern environment of the university and the surroundings. This is due to the novelty of the decision and the new mechanism for graduation. Instead of the stereotypical degree and job search, the student has become an entrepreneur who creates job opportunities.
The impact of university business incubators on the implementation of Ministerial Resolution 1275 study of the El-oued University incubator
Keywords: حاضنات الأعمال الجامعية; القرار الوزاري 1275; University business incubators; decision Ministerial number 1275